IKLIM ORGANISASI, MOTIVASI KERJA, DAN KEPUASAN UPAH TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN - Hadi, Nizarwan; Aulia, Aulia; Sari, Erita Yuliasesti Diah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Employee commitment is an important factor in improving organizational performance. There are several factors that affect employee commitment, one of which is the organizational climate.The organizational climate is an effective management device for integrating employee motivation with the tasks and objectives of the organization.The purpose of this study is to empirically examine the role of organizational climate, work motivation, and wage satisfaction on employee organizational commitment. The method used in this study is a quantitative method with a correlation approach. The participants of this study were permanent employees of company